DEXTROCARDIA ASSOCIATED WITH LEFT HEMIDIAPHRAGMATIC EVENTRATION - Saeed, Tahir; Mufti, Tariq Saeed (Journal of Ayub Medical College Abbottabad, 2004)
A rare case of dextrcardia in association with eventration of left hemidiaphragm who failed to thrive is presented. Growth retardation could not be attributed to these congenital anomalies.